(untitled) (La U Investiga, 2019)
Introduction: Spinal anesthesia for laparoscopic cholecystectomy has emerged as an alternative to general anesthesia Objective: To describe the results of spinal anesthesia in laparoscopic cholecystectomy. Method: A descriptive, longitudinal study was conducted at the Hospital Clínica Metropolitana, between January 2008 and June 2018, in 1118 patients who were administered spinal anesthesia with 0.5% bupivacaine, morphine and fentanyl to proceed to cholecystectomy. laparoscopic In them hemodynamic changes, analgesia, recovery and complications were determined. Descriptive statistics was applied and the data are expressed in percentages and arithmetic mean. Results: The mean age of the patients was 54 years. Of the patients under study, 17.88% presented hypotension as an intraoperative complication. Bradycardia occurred in 8.9% of patients. The two cardiovascular events recovered immediately with the use of vasopressor. The most frequent postoperative adverse events were right omalgia in 2.68% and vomiting in 1.78% of the total patients studied. In the postoperative period, the analgesic response without pain was in 99% of the total cases. All had a recovery without incident, at 24 hours they were discharged. Conclusions: Laparoscopic cholecystectomy with spinal anesthesia can be performed safely and satisfactorily without complications.